Resisting the Politics of Displacement in the San Francisco Bay Area: Anti-gentrification Activism in the Tech Boom 2.0 - Florian Opillard (European Journal of American Studies)
Drawing from an ongoing ethnographic work in the Tenants Movement in San Francisco, this article seeks to analyze both the gentrification context and its activist response during the year 2014. After a wave of evictions that the city has had to face in the years 2000, now called the first tech-boom, signs indicate that in 2013 and 2014, a strong influx of capital through companies of the tech industry has driven the phenomenal surge of evictions, buyouts and tenants harassment in the city. Focusing on two of the activist collectives and organizations that intend to fight this now called “tech-boom 2.0”, I describe the practical ways in which organizing collectively from weekly meetings, marches, rallies leads to the design by a city-scale coalition of pieces of legislation that crystalize and structure the progressive forces in San Francisco and the Bay Area.